1997
DOI: 10.1021/bi9625455
|View full text |Cite
|
Sign up to set email alerts
|

Properly Oriented Heparin−Decasaccharide-Induced Dimers Are the Biologically Active Form of Basic Fibroblast Growth Factor,

Abstract: Interaction of basic fibroblast growth factor (FGF-2) with heparin or heparan sulfate proteoglycans (HSPGs) is required for receptor activation and initiation of biological responses. To gain insight into the mechanism of activation of the FGF receptor by FGF-2 and heparin, we have used NMR, dynamic light scattering, and HSPG-deficient cells and cell-free systems. The first 28 N-terminal residues in FGF-2 were found to be highly mobile and flexible, consistent with the disorder found in both the NMR and X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 53 publications
3
57
3
Order By: Relevance
“…Taking advantage of the surface-exposed cysteine residues in the wild-type structure of FGF2, we performed oxidative cross-linking studies to test the proposed symmetrical mode of FGF2 dimerization in Fig. 2C, as this model predicts facile cross-linking between two FGF2 molecules (27). Under mild oxidative conditions, wild-type FGF2 showed very little oligomer formation in the presence and absence of heparin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking advantage of the surface-exposed cysteine residues in the wild-type structure of FGF2, we performed oxidative cross-linking studies to test the proposed symmetrical mode of FGF2 dimerization in Fig. 2C, as this model predicts facile cross-linking between two FGF2 molecules (27). Under mild oxidative conditions, wild-type FGF2 showed very little oligomer formation in the presence and absence of heparin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…B, two FGF molecules are oriented in trans to the axis of HLGAG in a "head-to-head" fashion (28). C, four FGF molecules interact both in cis and in trans with HLGAG (27). Note that, for the cis-interaction, the two FGF molecules are symmetrically related, as opposed to the dimer in A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For FGF2, the crystal structure with the highest resolution (PDB code 1bgf) showed disorder for the ®rst 19±20 N-terminal residues (Ago et al, 1991), con®rmed by NMR studies of complete FGF2 (PDB code 1rml), which showed disorder for the N-terminal 28 residues (Moy et al, 1996). For FGF1 the crystal structure with the highest resolution (PDB code 2afg) showed disorder for the N-terminal 9±10 residues (Blaber et al, 1996); for the NMR structure (PDB code 1rml) a molecule N-terminally truncated at residue 25 was used (Lozano et al, 1998).…”
Section: Acta Cryst (2001) D57 378±384mentioning
confidence: 87%
“…Several models have been proposed for the interaction between FGF2±heparin and its receptor Ruoslahti & Yamaguchi, 1991;Spivak-Kroizman et al, 1994;Kan et al, 1993;Guimond et al, 1993;. Previous work utilizing NMR demonstrated that FGF dimers in a symmetric tetramer are formed in the presence of an active heparin decasaccharide (Moy et al, 1997), suggesting that a cis-oriented dimer is the minimal biologically active structural unit of FGF2. Using de®ned heparin fragments and soluble FGF receptors further demonstrated that ligand dimerization can signi®cantly enhance the binding of FGF2 to FGFR1, the dimerization of the receptor and the induction of downstream signal transduction pathways (Safran et al, 2000).…”
Section: Introductionmentioning
confidence: 99%